2019
DOI: 10.1097/prs.0000000000005554
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Correction of Craniofacial Microsomia: Evaluation of Interventions in 565 Patients at Three Major Craniofacial Units

Abstract: Background: Craniofacial microsomia is characterized by an asymmetric hypoplasia of derivatives of the first and second pharyngeal arch, leading to a variety of phenotypic presentations. Studies on surgical correction of patients with craniofacial microsomia have small cohorts, leaving controversial opinions on the optimal treatment modality, the indication for surgery, and the optimal timing of surgery. The purpose of this study was to evaluate the types of, timing of, and total number of surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…[39][40][41] The largest retrospective case series of craniofacial microsomia was a multi-institutional collaboration reporting on the surgical interventions in 565 patients. 3 In this case series, only two patients underwent surgical treatment for facial nerve dysfunction: one had a cross-face nerve graft at 15 years of age, and the other received gold weights for lagophthalmos. Outcomes of these surgical interventions were not discussed.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[39][40][41] The largest retrospective case series of craniofacial microsomia was a multi-institutional collaboration reporting on the surgical interventions in 565 patients. 3 In this case series, only two patients underwent surgical treatment for facial nerve dysfunction: one had a cross-face nerve graft at 15 years of age, and the other received gold weights for lagophthalmos. Outcomes of these surgical interventions were not discussed.…”
Section: Discussionmentioning
confidence: 97%
“…1 First described in 1861, craniofacial microsomia is characterized by dysgenesis of the first and second branchial arches resulting in ipsilateral hypoplasia of the facial skeleton (i.e., mandible, maxilla, zygoma, and/or temporal bone), auricle, facial musculature, and subcutaneous tissues, with bilateral features in 5 to 30 percent of cases. [2][3][4][5][6] In addition to the classic soft-tissue and skeletal findings of craniofacial microsomia, cranial nerve anomalies may be present, most often of the facial nerve. Facial nerve dysfunction has been reported in 10 to 45 percent of cases, with involvement ranging from single branch paresis (most often of the marginal mandibular branch) to complete hemifacial paralysis.…”
mentioning
confidence: 99%
“…In conclusion, we have shown that in mild cases CFM does not have a progressive nature, thus, operative treatment can be postponed until skeletal maturity is reached if no other medical conditions require early intervention. Even though there have been some large multicenter studies published in recent years, 38,39 due to the rarity and the heterogeneity of the condition, future studies should be performed collaboratively between craniofacial centers and documentation of patients and their growth preferably using 3D photography should be done in a uniform fashion to enable true longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…36 In specific, the surgical management of Treacher Collins syndrome on average requires 3 surgical procedures and coordinated care between over 40 clinicians from 18 different disciplines. 37 Likewise, patients with bilateral craniofacial microsomia on average require 2.44 surgeries, 38 with a greater number of surgical corrections required for patients with more severe presentations. Virtual surgical planning use improves continuity of care by allowing different aspects of a patient's surgical care to be managed under 1 surgeon trained in orthognathic surgery.…”
Section: Discussionmentioning
confidence: 99%